PENERAPAN ACTIVITY BASED COSTING TERHADAP PERHITUNGAN HARGA POKOK PRODUKSI BERAS PADA KELOMPOK TANI NYIUR MELAMBAI DESA TAUGI DI KECAMATAN MASAMA KABUPATEN BANGGAI: PENERAPAN ACTIVITY BASED COSTING TERHADAP PERHITUNGAN HARGA POKOK PRODUKSI BERAS PADA KELOMPOK TANI NYIUR MELAMBAI DESA TAUGI DI KECAMATAN MASAMA KABUPATEN BANGGAI - Doloan, Arisanjaya (Universitas Muhammadiyah Luwuk Banggai, 2024)
Application of Activity-Based Costing to Calculate the Cost of Rice Production in the Nyiur Melambai Farmer Group, Taugi Village in Masama District, Banggai Regency. This research aims to determine and analyze the application of Activity Costing to Calculate the Cost of Rice Production in the Nyiur Melambai Farmer Group, Taugi Village in Masama District, Banggai Regency. In line with the research objectives, this research uses a qualitative descriptive research method, namely data obtained from interviews will be analyzed for the cost of goods produced in determining the cost of goods sold. The research results show that in the Activity Costing method, this is because all cost elements are considered, such as depreciation costs, costs for using equipment, and others. In the method used by the Nyiur Melambai Farmers Group, these are not taken into account. Of course, these costs which are often ignored should indeed need to be taken into account even though the depreciation costs are not cash spent, but are the amount of money that must be set aside or saved from the company's income in order to prepare or purchase equipment or machines. Meanwhile, determining the selling price still looks at the existing market price by calculating the cost of existing raw materials.